2005
DOI: 10.1152/ajprenal.00200.2004
|View full text |Cite
|
Sign up to set email alerts
|

Urea may regulate urea transporter protein abundance during osmotic diuresis

Abstract: Rats with diabetes mellitus have an increase in UT-A1 urea transporter protein abundance and absolute urea excretion, but the relative amount (percentage) of urea in total urinary solute is actually decreased due to the marked glucosuria. Urea-specific signaling pathways have been identified in mIMCD3 cells and renal medulla, suggesting the possibility that changes in the percentage or concentration of urea could be a factor that regulates UT-A1 abundance. In this study, we tested the hypothesis that an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…Diabetes Induced Renal Urea Transport Alterations Assessed With 3D Hyperpolarized 13 C, 15 the control kidney, (P < 0.0001) (Fig. 2).…”
Section: Figmentioning
confidence: 90%
See 2 more Smart Citations
“…Diabetes Induced Renal Urea Transport Alterations Assessed With 3D Hyperpolarized 13 C, 15 the control kidney, (P < 0.0001) (Fig. 2).…”
Section: Figmentioning
confidence: 90%
“…Thus, we speculate that this increase is to compensate for the reduced concentrating ability in the diabetic kidney. Likewise, as UT-A2 and UT-B compensate for the action of the each other, the increase observed in UT-B and thereby a decrease in UT-A2 may result from a challenge to restore inner medullary interstitial urea, which is disrupted even in the early stage of diabetes (11,13,15). Although changes are observed both in urea gradient and urea transporter expression, the NGAL marker included in this study indicated that no kidney injury can be seen in the early stages of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ammonia and urea concentrations of the rats with diabetes2 were normal, but rats with diabetes1 presented considerably higher urea (+401.5%) and ammonia (+90.9%) concentrations. These higher blood urea and ammonia concentrations in rats with diabetes1 are probably reflecting the higher rates of amino acid degradation (Squires et al, 1997), which also increase the urinary urea excretion (Kim et al, 2005). However, the increased urea excretion was combined with a much higher urinary volume and lower urinary urea concentrations (Kim et al, 2005).…”
Section: Treatment Of Datamentioning
confidence: 99%
“…These higher blood urea and ammonia concentrations in rats with diabetes1 are probably reflecting the higher rates of amino acid degradation (Squires et al, 1997), which also increase the urinary urea excretion (Kim et al, 2005). However, the increased urea excretion was combined with a much higher urinary volume and lower urinary urea concentrations (Kim et al, 2005). The high blood urea concentrations are, thus, the consequence of both higher amino acid catabolism and impaired renal function.…”
Section: Treatment Of Datamentioning
confidence: 99%